Balancing Technology and Clinical Skills: A Call to Preserve the Art of Medicine - Imran Ahmad,; Farooq Azam Rathore, (Journal of the Pakistan Medical Association, 2025)
21st-century medicine has seen incredible advancements in diagnostics, therapeutics and clinical care, with molecular and genetic breakthroughs offering hope for previously incurable diseases, thus reducing morbidity and mortality.1 However, this technological leap has inadvertently led to the decline in the art of clinical medicine, a compassionate, patient-centred approach based on clinical examination. Our predecessors, the esteemed physicians of the past, exemplified the true art of clinical medicine by developing compassionate and empathetic relationships built on trust and understanding.Their attentive listening, thorough physical examinations, and personalised care plans earned them deep respect within their communities. Continued..